Study on Genetic diversity of Frankia strains from symbiotic nodules of Myrica rubra - HE Xin-hua; CHEN Li-geng; HU Xi-qin; ZHANG Jian-ye (浙江大学学报. 农业与生命科学版)
Ten isolates of Frankia from symbiotic nodules of Myrica rubra were studied on their phenotypes and RFLP analyses of their PCR products amplified from 16S rDNA by restriction enzymes Hinf I and Hae Ⅲ. The results showed that there are differences not only in their phenotypes but also in their gene types among the ten isolates of Frankia. There are also differences in phenotypes and gene types among strains of Frankia isolated from the same nodule of Myrica rubra var. puji at different time which may be different gene groups. The results of their phenotypes and RFLP analyses of their PCR products amplified from 16S rDNA of ten isolates of Frankia from symbiotic nodules of Myrica rubra showed ample genetic diversity.